Radiologic evaluation of the maxillary sinus area before and after le fort I impaction surgery - Halawa, Atef Esmat (My University, 2005)
Bu retrospektif çalışmanın amacı Le Fort I maksiller gömme ameliyatına bağlı olarak maksiller sinus boyutlarında meydana gelen azalmayı ölçmektir. Çalışmanın materyalini 21 kız, 15 erkek, toplam 36 hastaya ait lateral sefalometrik filmler oluşturmaktadır. Bu filmler Marmara Üniversitesi Dişhekimliği Fakültesi Ortodonti Anabilim Dalının arşivinden elde edilmiştir. Çalışma grubunu oluşturan bireylerin yaş ortalaması 22.7 ± 2.96 yıldır. Çalışma grubuna seçilen bireylerin tümüne Le Fort I maksiller gömme operasyonu uygulanmıştır. Hastalar ameliyat öncesi ve sonrasında ortodontik tedavi görmüşlerdir. Maksiller sinus ölçümleri hastalardan ameliyat öncesi ve sonrası elde edilmiş olan lateral sefalometrik filmler üzerinde yapılmıştır. Hastaların 12’sinin ameliyat sonrası ortalama 15 aylık bir dönem sonunda alınmış takip röntgenleri de mevcuttur. Maksiller sinusün çeperi çizim kağıdı üzerinde çizildikten sonra bir tarayıcıdan geçirilerek bilgisayara aktarılmıştır. Maksiller sinüsün alanı AutoCAD R14 yazılımı kullanılarak dijital olarak ölçülmüştür. Ölçümlerin güvenilirliğini değerlendirmek için üç bağımsız gözlemcinin görev aldığı bir kör yöntem kullanılmıştır. Ameliyata bağlı olarak maksiller sinüs alanında meydana gelen değişiklikler eşleştirilmiş t- testi ile istatistiksel olarak değerlendirilmiştir. Çalışmada şu sonuçlara ulaşılmıştır: 1- Çalışma grubunu oluşturan bireylerde maksilla ortalama 3 mm civarında gömülmüştür. 2- Maksilladaki gömülme parallel bir şekilde gerçekleşmiştir, 3- Maksiller sinüs alanı ameliyat sonrasında ortalama 1.69 cm2±1.07 cm2 azalmıştır. 4- Ameliyat sonrasındaki ortalama 15 aylık sürede maksiller sinüs alanı ortalama 0.52 cm2 ± 0.53 cm2 artmıştır. The aim of this retrospective study was to measure the changes in the maxillary sinus size due to Le Fort I maxillary impaction surgery. The study material included the lateral cephalometric films of 36 patients (21 female and 15 males). They were selected from the archieves of the orthodontic department in the Dental Faculty of Marmara University. The average age of the patients was 22.7 ± 2.96 years. The selected cases were surgically treated patients with Le Fort I maxillary impaction. The patients have been treated orthodontically before and after surgery. The maxillary sinus measurements were made on the lateral cephalometric films of the patients which were obtained before and after surgery. For 12 patients of these patients, lateral cephalometric films taken in the postsurgical period were also available. These cephalograms were obtained on average 15 months after surgery. Maxillary sinus areas were traced on the lateral cephalograms and then the tracings were scanned for transferal to the computer. AutoCAD R14 software was used to digitally measure the size of the maxillary sinus. A blind method involving three independent viewers was used to assess the reliability of the measurements. Paired t-test was used to evaluate the changes in the maxillary sinus area due to surgery. The results of our study were: 1- Maxilla was impacted about 3 mm on average in the study group. 2- The inclination of the palatal plane did not change significantly during impaction. 3- Maxillary sinus area significantly decreased on average by 1.69 cm2±1.07 cm2 after surgery. 4- During the average postsurgical period of 15 months, maxillary sinus area increased by 0.52 cm2 ± 0.53 cm2.
Keywords: Ortodonti